THE INFLUENCE OF INFORMATION SERVICES THROUGH ANIMATED FILM MEDIA ON MENTAL HEALTH IN CLASS XI IIS STUDENTS OF SMA NEGERI 1 BINJAI LANGKAT DISTRICT - Yudha Wastuti, Sri Ngayomi; Sekar Mawarni, Ayu Hanung (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to determine the effect of information services through animated film media on the mental health of class XI IIS students at SMA Negeri 1 Binjai, Langkat Regency for the 2022/2023 academic year. This type of research uses quantitative experimental methods, namely one group pretest and posttest design. The subject of this research was class XI IIS 2 with a sample size of 33 students determined using purposive sampling. This research uses a questionnaire instrument as a measuring tool and uses validity tests, reliability tests, and paired T tests. Based on the results of research conducted: 1) there are differences in students' mental health before being given information services through film media with the pretest score results showing that students' mental health is in the low category. 2) there are differences in students' mental health after being given information services through film media with the pretest score results showing that students' mental health has a high category score. 3) there is an effect of increasing information services through film media using the paired T test with a sig (2-tailed) value of 0.000 < 0.05 and the difference in the average pretest value and the difference in the average pretest value of 89.6667 > from the average posttest value of 125.5758 which shows that there is a significant difference between the pretest and posttest, then Ho is rejected and Ha is accepted, which means that there is an influence of information services through film media on the mental health of Class XI IIS students at SMA Negeri 1 Binjai Langkat Regency for the 2022/2023 academic year.